2017
DOI: 10.1093/bioinformatics/btx054
|View full text |Cite
|
Sign up to set email alerts
|

Automated cell type discovery and classification through knowledge transfer

Abstract: MotivationRecent advances in mass cytometry allow simultaneous measurements of up to 50 markers at single-cell resolution. However, the high dimensionality of mass cytometry data introduces computational challenges for automated data analysis and hinders translation of new biological understanding into clinical applications. Previous studies have applied machine learning to facilitate processing of mass cytometry data. However, manual inspection is still inevitable and becoming the barrier to reliable large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…We compared the proportions of all cell subsets estimated by MetaCyto with the original manual gating results and found that MetaCyto estimations are highly consistent with the manual gating result (Figure 2A-C). We compared our estimations to two existing methods, flowDensity (Malek et al, 2015) and ACDC (Lee et al, 2017), which can also identify pre-defined cell populations. Our results suggest that MetaCyto’s quantification of both major and rare populations were more accurate than FlowDensity’s (Figure 2D,E).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the proportions of all cell subsets estimated by MetaCyto with the original manual gating results and found that MetaCyto estimations are highly consistent with the manual gating result (Figure 2A-C). We compared our estimations to two existing methods, flowDensity (Malek et al, 2015) and ACDC (Lee et al, 2017), which can also identify pre-defined cell populations. Our results suggest that MetaCyto’s quantification of both major and rare populations were more accurate than FlowDensity’s (Figure 2D,E).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the performance of the LDA classifier, we compared LDA with two recent state‐of‐the‐art methods for classifying CyTOF data, ACDC and DeepCyTOF . We used the AML, BMMC and PANORAMA datasets (used by ACDC) and the Multi‐Center dataset (the only available dataset used by DeepCyTOF).…”
Section: Resultsmentioning
confidence: 99%
“…For the BMMC dataset, we applied the LDA classifier to classify all 24 cell populations, resulting in ~96% accuracy and 0.85 median F1‐score. To have a fair comparison with ACDC, we also considered four populations as unknown then classified only 20 cell populations. In both cases, LDA outperformed ACDC, specially based on the median F1‐score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern instruments including both flow and mass cytometers are now capable to quantify between 20 and 50 proteins, leading to high-dimensional data that are impossible to exhaustively explore by manual analysis. Automated cell classification has also been applied to mass cytometry by time of flight (CyTOF) data (16). A number of these have been compared in the open competition set-up by the Flow Cytometry: Critical Assessment of Population (FlowCAP) consortium (1) and many developments have followed as a result (12)(13)(14) as reviewed in Saeys et al (15).…”
mentioning
confidence: 99%